MORTALIDADE POR NEOPLASIA DE MAMA: UMA ANÁLISE NAS MICRORREGIÕES DO RIO GRANDE DO SUL NO PERÍODO DE 1995 A 2007 - Heimerdinger, Ana P.; Battisti, Iara D. E.; Cichorski, Mariane; Cassol, Vanessa J. (Salão do Conhecimento, 2013)
Resumo